Álbum digital de aves da Amazônia como recurso didático no ensino de ciências na Escola Miguel Bitar no município de Breves-PA - ANJOS, Paulo José Romão dos (2024)
This course conclusion work aimed at the development of a digital album of Amazonian birds, with the intention of using it as a teaching resource in science teaching, in order to sensitize students about the importance of Amazonian birds and approximate reality of the students in the teaching process, and through the use present the morphological characteristics, geographical distribution and the scientific classification of the group, and the relationship between the birds, the environment and humans. Data were obtained by applying questionnaires for students, which were submitted to analysis and evaluated the acceptance and effectiveness of digital album as a teaching resource and the theme birds as a generator. Through data analysis results showed that the teaching resource aroused the interest of students by class, making the most participatory same, thus contributing in the teaching-learning process. It is concluded that the photo book of birds of the Amazon, has been well accepted as a teaching resource in science teaching. In this sense as any teaching resource, comes to add and complement the traditional classroom, adopting new teaching methods bring good results. Thus, arouse students' attention, making interactive content, promoting teaching and learning.